Self-assembly of oriented antibody-decorated metal-organic framework nanocrystals for active-targeting applications - Alt, Karen (2022)
Antibody (Ab)-targeted nanoparticles are becoming increasingly important for precision medicine. By controlling the Ab orientation, targeting properties can be enhanced; however, to afford such an ordered configuration, cumbersome chemical functionalization protocols are usually required. This aspect limits the progress of Abs-nanoparticles toward nanomedicine translation. Herein, a novel one-step synthesis of oriented monoclonal Ab-decorated metal-organic framework (MOF) nanocrystals is presented. The crystallization of a zinc-based MOF, Zn2 (mIM)2 (CO3 ), from a solution of Zn2+ and 2-methylimidazole (mIM), is triggered by the fragment crystallizable (Fc) region of the Ab. This selective growth yields biocomposites with oriented Abs on the MOF nanocrystals (MOF*Ab): the Fc regions are partially inserted within the MOF surface and the antibody-binding regions protrude from the MOF surface toward the target. This ordered configuration imparts antibody-antigen recognition properties to the biocomposite and shows preserved target binding when compared to the parental antibodies. Next, the biosensing performance of the system is tested by loading MOF*Ab with luminescent quantum dots (QD). The targeting efficiency of the QD-containing MOF*Ab is again, fully preserved. The present work represents a simple self-assembly approach for the fabrication of antibody-decorated MOF nanocrystals with broad potential for sensing, diagnostic imaging, and targeted drug delivery.